(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
The key problem that determines the prognosis and tactics of surgical treatment in this category of patients is the development of pulmonary arterial hypertension (PAH), a pathological condition characterized by a progressive increase in pulmonary vascular resistance and pressure in the pulmonary artery due to chronic hypervolemia of the pulmonary circulation. According to current epidemiological data, PAH associated with congenital heart defects is detected in 1.6–12.5 per million population in the general population, but among patients with uncorrected septal defects with a left-right shunt, its incidence reaches 30–50% during the first two years of life. The pathophysiological progression of pulmonary hypertension in septal defects includes successive morphological stages according to the Heath-Edwards classification: from initial hypervolemic hypertension with reversible medial hypertrophy of the pulmonary arterioles to irreversible obliterating pulmonary arteriopathy with plexiform lesions - Eisenmenger syndrome, in which the pressure in the pulmonary artery reaches or exceeds the systemic level, the direction of the shunt is inverted, and the standard surgical correction of the defect becomes impossible or extremely high-risk.